Mediterranean and North Pontic Greek Imports in the Nomadic Burials of the Lower Volga Region and Foothills of South Urals of the 4th — First Third of the 3rd Century BC - Treister, M.Yu. (Археологія і давня історія України, 2021)
The analysis of archaeological sources shows that in the second half of the 4th century BC imported beads and pendants made of glass, frit and amber reach the nomads of the Lower Volga and South Urals, and a little later, at the turn of the 4th and in the first third of the 3rd century BC — in addition, Greek pottery and possibly vessels made of precious metals, alabaster and onyx. Olbian bronze «borystheni» of the late 4th—3rd centuries BC also were found into the Lower Volga region. If for the 5th and most part of the 4th century BC imports that entered the South Urals were mainly represented by products of the Achaemenid circle, then after the fall of the Achaemenid state and the resulting geopolitical changes in the Lower Volga region and the South Urals imports began to be distributed from (via) the North Pontic region.